IMPLEMENTASI PROGRAM SCHOOL IMPROVEMENT PADA COMMUNITY DEVELOPMENT (CD) PT. RIAU ANDALAN PULP AND PAPER (RAPP) PANGKALAN KERINCI, PELALAWAN RIAU - Erma Saputri Silaban; Rusmadi Awza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The School Improvement program is a Corporate Social Responsibility program run by PT. RAPP through Community Development. School Improvement program has 3 objectives namely, improving the quality learning system, helping to improve School Accreditation and realization of Adiwiyata schools in the partner school. School Improvement carried out by the Community Development PT. RAPP as well as seeing the impact of the School Improvement program on School and seeing developments is that occured before and after implementation.This study uses qualitative research methods. In determining informants, this study uses purposive methods. Data collection techniques in this studies consist of interviews, documentation and observation. Meanwhile, for data analysis technique used in this research is descriptive analysis according to Huberman and Miles. To check the validity of the data, researchers used participation extension and triangulation.The results of this study indicate that Community Development PT. RAPP carried out four stage of implementation in implementing the School Improvement program. The first stage is to select a location, The second stage is socialization, where at this stage Community Development explains in more detail about the School Improvement program for the parties involved in launching the school improvement program and also uses online media. The third stage is Community based development where at this stage the implementation of the school improvement program has been running in partner schools,And the last stage namely Community independence where at this stage the Community Development provides assistance to partner schools. As for the impact of the school improvement program in schools when helping teachers in effective learning and being able to use media leaarning. Besides that, for the principal, being able to find out how to improve school acreditation through the training that was carried out. And preserving the partner school environment with the implementation of adiwiyata. Meanwhile, the company itself get a positive image in the eyes of the community because it always pays attention to the life of the community around the company’s operational area, especially in education. Keyword : Program Implementation, School Improvement, CD PT.RAPP